2021
DOI: 10.3390/ijms22083915
|View full text |Cite
|
Sign up to set email alerts
|

Key Disease Mechanisms Linked to Alzheimer’s Disease in the Entorhinal Cortex

Abstract: Alzheimer’s disease (AD) is a chronic, neurodegenerative brain disorder affecting millions of Americans that is expected to increase in incidence with the expanding aging population. Symptomatic AD patients show cognitive decline and often develop neuropsychiatric symptoms due to the accumulation of insoluble proteins that produce plaques and tangles seen in the brain at autopsy. Unexpectedly, some clinically normal individuals also show AD pathology in the brain at autopsy (asymptomatic AD, AsymAD). In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 133 publications
2
24
0
1
Order By: Relevance
“…However, further studies are needed to evaluate this association. Interestingly, previous analysis of DEGs between the entorhinal cortex of AD patients and healthy controls also showed alteration of the retrograde endocannabinoid signaling pathway and predicted GATA1 and GATA2 as the upstream regulators of the identified DEGs in AD [74]. Our results here identified altered pathways in each brain region of AD patients and shared pathways between AD sensitive brain regions.…”
Section: Discussionsupporting
confidence: 70%
“…However, further studies are needed to evaluate this association. Interestingly, previous analysis of DEGs between the entorhinal cortex of AD patients and healthy controls also showed alteration of the retrograde endocannabinoid signaling pathway and predicted GATA1 and GATA2 as the upstream regulators of the identified DEGs in AD [74]. Our results here identified altered pathways in each brain region of AD patients and shared pathways between AD sensitive brain regions.…”
Section: Discussionsupporting
confidence: 70%
“…A recent autopsy study indicated that p-tau at threonine 217 (p-tau217) was the most important phosphorylation site in the differentiation between Alzheimer’s disease and control brain tissue ( Wesseling et al, 2020 ), and plasma p-tau217 has been considered a biomarker of AD ( Thijssen et al, 2021 ). Aβ and tau protein deposition can affect signal and substance transmission between neurons, leading to neuronal degeneration and death ( Bottero et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, nearly 50 million people are affected by AD and other dementias and this number is projected to continue to double every 20 years ( Grande et al, 2020 ). Despite this widespread prevalence, pathophysiology is still poorly understood ( Bottero et al, 2021 ) and neuronal destruction “cannot be prevented, slowed, or cured” ( Leandrou et al, 2020 , p.176).…”
Section: Introductionmentioning
confidence: 99%